Pemberdayaan Usaha Mikro Perempuan: Peran Kunci Literasi Risiko Berbasis Syariah - Dharma, Budi (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2024)
Sharia-based risk management goes beyond conventional risk management practices by aligning with Islamic principles and ethics. It involves identifying, assessing, and mitigating risks while ensuring compliance with sharia law. The research tries to analyse the results of integrating these principles into micro-enterprise management, involving at least 40 women entrepreneurs in Medan City. The research used a qualitative approach, with data collection obtained from observations and interviews with women entrepreneurs. The population is comprised of juice businesses owned by women in the city of Medan, with data collection techniques using area sampling. The results of the analysis found at least 5 critical risks. The results of the analysis show the role of sharia-based risk literacy in empowering women's micro-enterprises, where a strong understanding of Sharia principles can be a key factor in increasing the success and resilience of women's micro-enterprises. With good risk literacy, women micro-entrepreneurs can manage risks more effectively, make wiser decisions, and develop their businesses in a way that complies with sharia principles.